PENINGKATAN KUALITAS PELAYANAN PUBLIK MELALUI APLIKASI PENGADUAN SP4N-LAPOR! PADA KEMENTERIAN PENDAYAGUNAAN APARATUR NEGARA DAN REFORMASI BIROKRASI - Serly Wulandari (Jurnal Ilmiah Wahana Bhakti Praja, 2023)
SP4N-LAPOR complaint application! is a single application in managing nationally integrated public service complaints that aim to improve the quality of public services. Until 2022, 8.61% of central/regional agencies have not been connected to SP4N-LAPOR!, 30.2% of the total complaint reports have not been resolved and the value of satisfaction with the SP4N-LAPOR! admin only 54%.. This study aims to determine the improvement in the quality of public services that have been carried out by the Ministry of Administrative and Bureaucratic Reform through the SP4N-LAPOR! Complaint Application. This research uses a descriptive method with a qualitative approach. The conceptual framework of the research uses Parasuraman's Electronic Service Quality theory (2005) with dimensions including: efficiency, fullfillment, system availability and privacy. Source of data in the form of primary data and secondary data. Data collection techniques through interviews, observation and document study. Data analysis techniques through data reduction, data presentation to draw conclusions. The results of the study show that improving the quality of public services through the SP4N-LAPOR! complaint application still not running optimally where from the efficiency dimension, the stages of how to report are not included in how to access SP4N-LAPOR! via sms to number 1708; fullfillment dimension, there is still management of SP4N-LAPOR! which are not in accordance with PAN-RB Ministerial Regulation No. 62 of 2018; the system avaibility dimension, there are still agencies that are not yet connected to SP4N-LAPOR! due to network constraints in the region; as well as the privacy dimension, where the guarantee of the security and confidentiality of the reporter's data has been carried out by involving various parties and special features have been made in SP4N-LAPOR!.